Effectiveness of a combination of acupressure and foot bath on Ankle Brachial Index (ABI) in type II diabetic patients - Deby, Krissantus Adimas; Ta'adi, Ta'adi; Windiarti, Sri Endang (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Diabetes is a chronic disease that will be suffered for life and can have an impact on complications, one of which is Peripheral Arterial Disease (PAD) which is characterized by a decrease in the value of the Ankle Brachial Index (ABI) and is the main cause of the increasing number of gangrene incidents and amputations. To prevent these complications, it is necessary to have therapy that can increase the value of the Ankle Brachial Index (ABI), which is by combining acupressure therapy and warm water foot soak (hydrotherapy). Purpose: To analyzing the effectiveness of the combined therapy of acupressure and warm water foot soak towards Ankle Brachial Index (ABI) value in type II diabetes mellitus. Methods: Using a quasi-experimental design with a pretest-posttest design approach with 51 participant. The participant were taken using simple random sampling technique and divided into 3 intervention groups. The first group is acupressure (n = 17), the second group is warm water foot soak (n = 17) and the third group is a combination of acupressure and warm water foot soak (n = 17). The normality test in this study was conducted using the Shapiro Wilk test, the dependent t test was used to determine any changes in each group while comparing the effectiveness of Ankle Branchial Index (ABI) values of each group using the one way anova test. Results: The use of acupressure therapy can have an effect on the value of the Ankle Brachial Index (ABI) with a significance value of p:  .000. The group receiving warm water foot soak therapy also experienced changes but the change in the Ankle Brachial Index (ABI) value was not too significant because the significance value was obtained p:  0.002. While in the group with the combination of acupressure and warm water foot bath has a significance value of p: 0.000 Conclusion: The combination therapy of acupressure and warm water foot soak provides an effective influence on the ankle branchial index with a significance value of p: 0.000 (p < 0.05) compared to warm water foot soak therapy which has a significance value of p: 0.002. (p< 0,05). By combining acupressure therapy and warm water foot soak, sclerosed blood vessels can stretch due to the effect of heat which causes vasodilation of blood vessels which has an impact on smooth blood flow and can carry oxygen and nutrients well, especially to the feet.